PHYSICAL INDICES OF ORAL FLUID IN CHILDREN OF SCHOOL AGE WITH DIFFERENT DENTAL STATUS - Kaskova, L.F.; Popyk, K.M.; Ulasevych, L.P. (World of Medicine and Biology, 2019)
The study of the oral fluid physical characteristics in 6-16 years-old children is important for identifying the causes of caries and determining the main directions of preventive measures in each age period of schoolchildren. Studies have shown that caries in school-age children occurs against a background of oral fluid parameters deterioration compared to healthy children: reduced salivation rate, increased viscosity, and the decreased hydrogen index of oral fluid, which should be taken into account when carrying out preventive work to reduce caries.
Keywords: children; caries; intact teeth; physical indices of oral fluid